Beyond Atherosclerosis and Fibromuscular Dysplasia: Rare Causes of Renovascular Hypertension. Issue 4 (30th August 2021) - Persu, Alexandre; Canning, Caitriona; Prejbisz, Aleksander; Dobrowolski, Piotr; Amar, Laurence; Chrysochou, Constantina; Kądziela, Jacek; Litwin, Mieczysław; van Twist, Daan; Van der Niepen, Patricia; Wuerzner, Gregoire; de Leeuw, Peter; et al.
Abstract : Renovascular hypertension is one of the most common forms of secondary hypertension. Over 95% of cases of renovascular hypertension are due either to atherosclerosis of the main renal artery trunks or to fibromuscular dysplasia. These two causes of renal artery stenosis have been extensively discussed in recent reviews and consensus. The aim of the current article is to provide comprehensive and up-to-date information on the remaining causes. While these causes are rare or extremely rare, etiologic and differential diagnosis matters both for prognosis and management. Therefore, the clinician cannot ignore them. For didactic reasons, we have grouped these different entities into stenotic lesions (neurofibromatosis type 1 and other rare syndromes, dissection, arteritis, and segmental arterial mediolysis) often associated with aortic coarctation and other arterial abnormalities, and nonstenotic lesions, where hypertension is secondary to compression of adjacent arteries and changes in arterial pulsatility (aneurysm) or to the formation of a shunt, leading to kidney ischemia (arteriovenous fistula). Finally, thrombotic disorders of the renal artery may also be responsible for renovascular hypertension. Although thrombotic/embolic lesions do not represent primary vessel wall disease, they are characterized by frequent macrovascular involvement. In this review, we illustrate the most characteristic aspects of these different entities responsible for renovascular hypertension and discuss their prevalence, pathophysiology, clinical presentation, management, and prognosis.